Chlorine-doped SnO2 hydrophobic surfaces for large grain perovskite solar cells. Issue 33 (16th July 2020) - Gong, Wenxiao; Guo, Heng; Zhang, Haiyan; Yang, Jian; Chen, Haiyuan; Wang, Liping; Hao, Feng; Niu, Xiaobin
Abstract : Both wetting and non-wetting tin oxide SnO2 were spin-coated and the non-wetting electron transport layer demonstrated a larger perovskite and higher power conversion efficiency. Abstract : Planar-heterojunction lead halide perovskite solar cells (PSCs) have attracted considerable attention because of their simple and low-temperature fabrication process. Unfortunately, the electron transport layer (ETL) in these planar devices still suffer low electron mobility due to inefficient photoelectron extraction and carrier recombination, leading to low stable efficiency with high J – V hysteresis. Here, we prepared chlorine-capped tin oxide nanocrystals (SnO2 -Cl) by facile treatment of SnO2 nanoparticles with chloroform-D/2-methoxy ethanol solvent. By introducing halogen (Cl), the hydrophobic surface increases the grain size and crystallinity of perovskites, which dramatically reduces the charge trap density and suppresses the charge recombination. Combining the high work function, SnO2 -Cl as an ETL exhibits superior electronic properties by mitigating non-radiative recombination with faster charge carrier transfer. The results show that SnO2 -Cl based planar-heterojunction perovskite solar cells produce remarkably higher performances compared with untreated SnO2, increasing the power conversion efficiency (PCE) from 15.07% to 18.1% free of hysteresis. This simple method, providing the effect of halogen modified electron transport layer interface, paves the way for its application in interface engineering on ETL/perovskites for PSCs with enhanced photovoltaic performance.